Denoised inflation: A new measure of core inflation - Muhammad Nadim Hanif; Javaid Iqbal; Syed Hamza Ali; Muhammad Abdus Salam (Journal of Central Banking Theory and Practice, 2020)
Existing measures of core inflation ignore a part of 'should be' the core inflation. Exclusion based measures 'exclude' a part of persistent inflation inherently existing in the excluded part whereas filter based measures 'filter-out' the cyclical part also rather than the irregular component only. This study proposes a new idea to define and measure core inflation - noise free inflation or denoised inflation. As against considering only trend to define core inflation, this study proposes using cyclical component also to be part of core inflation. If core inflation is to be useful, for monetary policy making, as an indicator of underlying inflation, it has to include demand related component of inflation associated with current economic cycle. By using wavelet analysis approach to decompose seasonally adjusted price index into noise, cyclical component and trend, we estimate a denoised inflation series for Pakistan for the period July 1992 to June 2017. Since denoised inflation passes 'statistical' as well as 'theoretical' tests necessary for a series to be core inflation, we think it can be used as a new core inflation measure for Pakistan. This can also be estimated and tested for any country.
Keywords: C19; E31; E52; 330; Estimation of Cyclical Component; Inflation; Monetary Policy